Information literacy of LIS students at the University of Zagreb: pros or just average millenials - Hebrang Grgić, Ivana (Array, 2013)
The information literacy (IL) movement has grown dramatically over the past quarter century. Although the concept has entered the discourse of different disciplines, domains and landscapes, there is little doubt that IL has been the most explored and analysed in the educational sector. In the higher education sector, the emphasis in IL initiatives and curricula is on acquiring, developing and demonstrating individual skills and competencies, which will support independent lifelong learning, critical thinking and problem solving. For LIS students, however, the rationale and goals underlying IL integrated in the course of their studies is much more substantial and wider. In addition to become information literate themselves, LIS students have to be fully aware of the importance of IL as a concept, understand its relevance in contemporary societies and have to learn about main aspects of teaching IL. Regardless whether LIS students have attained information skills and practices by studying library and information science, or whether they have been attending IL courses, the question of transferability of IL to learning situations remains open. This paper presents a sub-study that explores the transferability of IL competencies to the overall research experience of LIS students and the application of IL competencies in fulfilling course assignments. The survey of LIS students was conducted at the Department of Information and Communication Sciences, Faculty of Humanities and Social Sciences, University of Zagreb. It is part of wider, international survey involving 21 countries with the aim of comparing LIS students’ IL in different countries and societies. The survey instrument was the same for all the countries – an online questionnaire with 17 questions on IL. The purpose of the main survey conducted on international level is to find out about LIS students’ research experience, information behaviour and information literacy skills, as well as to correlate them with the students’ status, their age, gender and GPA. Questionnaire was sent to 498 available e-mail addresses of undergraduate students at the Department of Information and Communication Sciences, University of Zagreb. Response rate was 40% (199 answers, 110 of them complete answers). Research questions pertained to the assignment types of LIS students, attitudes about initializing search processes for course related assignments, evaluation of search results, study practices applied during course-related assignments, priorities in completing assignments, tools they use etc. In the last question, students were asked if they had any comments to the topic and/or to the questionnaire. According to the comments, the survey has already been useful for participating students. Results of the survey will provide insight into the transferability of IL competencies applied for fulfilling course assignments of LIS students. IL competencies of this group of students is often assumed, but not explored. Such insights can be useful for teachers, mentors and librarians to determine LIS students’ real level of IL, evaluate approaches and revise, if necessary existing approaches in teaching IL. Furthermore, such insights will contribute to research issues of IL transferability, and specifically address the question whether courses that raise awareness and impart knowledge about IL contribute to its efficient transferability. As an additional value of the paper, IL of LIS students is compared to IL of average millenials, based on literature.